Understanding economics - Allsopp, Vicky 1946- (Routledge, 1995)
Economic issues exert a considerable pressure on everyday life. Yet, economic theory is often communicated as removed and difficult with little relation to real-life situations. Understanding Economics shows that this is not the case. In so doing, the book presents an accessible and alternative introduction to economics. The book is designed to illustrate the usefulness, versatility and relevance of economics. The author conveys how economics is concerned with a broad range of diverse matters, from economic systems as a whole, to particular issues, such as family planning, the stock market, pricing of shares or the non-market allocation of education and blood. The work provides an alternative view of traditional issues as well as an analysis of areas not normally covered. Understanding Economics is reader-friendly in both style and content and requires no prior knowledge of economics and minimal mathematics.